POTENTIAL, ECOLOGY AND FUTURE DEVELOPMENT OF ATONG PLANT (Parinarium glaberimum, Hassk) ON THE ISLAND OF SAPARUA - MALUKU - Johan Markus Matinahoru (Jurnal Sylva Scienteae, 2023)
The purpose of this study was to determine the potential and ecology of the Atong (Parinarium glaberimum) on Saparua Island, Central Maluku Regency. The method used for data collection of the  plants  number was the plot method, and for data analysis of vegetation was the Vegetation Value Index (VVI). The results of the research showed that the potential of atong plants in Saparua Island was classified as low density with an average number of 67 individual plants per hectare in each sample village. Atong plants are found growing and developing on the regosol soil at 100 - 300 meters from the coastline. Atong plant seeds are generally used by people to cure stomachaches, preservation of fish and also to prevent or to repel mosquitoes.